Ionospheric F‐Layer Scintillation Variabilities Over the American Sector During Sudden Stratospheric Warming Events - Hailun Ye; Xianghui Xue; Tao Yu; Yang‐Yi Sun; Wen Yi; Chi Long; Weifan Zhang; Xiankang Dou (Space Weather)
Abstract The present study investigates the ionospheric F‐layer scintillation responses in the American sector (90°W–0°, ±50° dip latitude) during the Northern Hemisphere winter sudden stratospheric warming events of 2007–2008, 2008–2009, 2009–2010, and 2012–2013. The scintillation data used in this work are obtained from the radio occultation observations of the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) mission. The important results of this study are described as follows: the occurrence altitude and rate of ionospheric F‐layer scintillation over the American sector decrease by an average of 13.48 km and 17%, respectively, during the sudden stratospheric warming (SSW) periods compared with the pre‐SSW periods. We find that ionospheric F‐layer scintillation over the American sector shows similar inhibitory responses to each SSW event, although these SSW events have diversities in some aspects, such as SSW types and solar and geomagnetic activities. To our knowledge, this study is the first to discover that an SSW event under low solar activity, including a minor warming event, can obviously affect the generation of ionospheric irregularities. Additionally, the types of SSW events may influence the decrease in altitude but not the occurrence rate. The decreased plasma vertical drift during prereversal enhancement, together with the changed meridional wind, are the possible mechanisms for the above results. In addition, we find that the enhanced planetary wave and lunar semidiurnal tide activities may be responsible for the decreases in the occurrence rate of ionospheric F‐layer scintillation before the peak warming of the 2008–2009 and 2009–2010 SSW events.